Examining the Militancy of the Apostle Paul in Fulfilling God's Calling as a Preacher of the Gospel - Imron Widjaja; Hye Kyung Park (Journal of Religious and Socio-Cultural, 2025)
This article explores the Apostle Paul’s commitment to fulfilling God’s calling as a preacher of the gospel. It emphasizes his loyalty to God and examines how his understanding of God’s call shaped his militant approach to evangelism. This study also seeks to understand how Paul’s model of mission work may still be relevant today. The article aims to examine the meaning of God’s call to the Apostle Paul, how he interpreted it, and how this impacted his militancy in preaching the gospel. Additionally, it evaluates whether Paul’s approach to evangelism can be applied in current missionary work. The study uses a descriptive-qualitative research method, with a hermeneutical approach to interpret Paul's experiences and mission as recorded in the New Testament. The study concludes that the Apostle Paul’s commitment and interpretation of God’s call led him to carry out his ministry with exceptional militancy. His personal sacrifices and his ability to face hardships in preaching the gospel exemplify his dedication. Furthermore, Paul’s model of evangelism, based on humility, love, and sacrifice, is still relevant today. This article contributes by offering a deeper understanding of Paul’s evangelistic zeal and providing a model of commitment and perseverance that modern evangelists can adopt. It demonstrates how Paul’s ministry continues to inspire and guide contemporary Christian mission work.